320 rue St Jacques The Diary of Madeleine Blaess - Michallat, Wendy (White Rose University Press, 2018)
"Madeleine's diary is unique as she wrote it to record as much as she could about everyday life, people and events so she could use these written traces to rekindle memories later for the family from whom she had been parted. Many diaries of that era focus on the political situation. Madeleine's diary does reflect and engage with military and political events. It also provides an unprecedented day-by-day account of the struggle to manage material deprivation, physical hardship, mental exhaustion and depression during the Occupation. The diary is also a record of Madeleine's determination to achieve her ambition to become a university academic at a time when there was little encouragement for women to prioritise education and career over marriage and motherhood. Her diary is edited and translated here for the first time. Dr Wendy Michallat was born in West Yorkshire. She studied at the Universities of Warwick and Nottingham and lectures in the School of Languages and Cultures at the University of Sheffield. She researches and teaches French cultural history, life-writing and popular culture and has published on diverse subjects including cartoon art, women's football and first-wave French feminism. Readers may prefer to download and cite from the PDF version of this book. This has a specific DOI and has a fixed structure with page numbers. Guidance on citing from other ebook versions without stable page numbers (Kindle, EPUB etc.) is now usually offered within style guidance (e.g. by the MLA style guide, The Chicago Manual of Style etc.) so please check the information offered on this by the referencing style you use."